Pengaruh PDRB, Inflasi dan Dana Pihak Ketiga terhadap Pertumbuhan Kredit PT. BPD Bali - Megawati, Ida Ayu Putu; Kesuma, I Ketut Wijaya (E-Jurnal Manajemen, 2014)
Credit are loans given by banks to those in need of funds. Revenue is dominated by bank lending as the bank's main advantage is obtained from the difference between lending and deposit rates. There are several factors that affect bank lending such as GDP, inflation and Third-Party Funds. The purpose of this study was to determine the effect of GDP, inflation, and Third-Party Funds on credit growth. This research was conducted at PT. Bank Pembangunan Daerah Bali. Sources of data obtained from the publication of the financial statements of BPD Bali and Bali Regional Economic Studies published by Bank Indonesia. Methods of data collection is done through nonparticipant observation and analysis techniques are used path analysis. Based on the results of the analysis found that GDP positive and significant impact on Third-Party Funds, inflation is positive and significant effect on Third-Party Funds. Third-Party Funds negative and significant effect on credit growth, GDP negative and no significant effect on credit growth, and the last inflation positive and significant effect on credit growth.
Keywords: GDP; Inflation; Deposits; Credit Growth